Approaches Related to the GHG Emission Assessment in the Livestock Sector and Mitigation Measures - K. Akamati; G. P. Laliotis (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
Livestock is one of the major contributors to climate change through emissions of greenhouse gases. Future global emissions are anticipated to rise significantly in response to the growing demand for animal products. Meeting human demand for animal products and eliminating the negative effects of livestock on the environment may depend heavily on the co-existence of extensive and intensive systems. Nonetheless, it is crucial to estimate greenhouse gas emissions from farm animal species at the national level to investigate additional mitigation strategies. Approaches related to the Tier 1, 2, and 3 methodologies of IPCC standards could be useful in this evaluation. The system boundaries, the expression units of the results, and the level of methodology complexity that are applied affect the computation of the final emissions estimations in studies using Tier approaches. Nevertheless, by implementing such evaluations, various scenarios can be investigated and further expanded to eliminate GHG emissions from livestock and to develop more environmental policies at the national level. The present report aims to briefly highlight the impact of livestock on GHG emissions, the contribution of intensive and extensive systems to these emissions, the methodologies recommended by the IPCC for the assessment of GHG emissions and recent results at the country level related to the implementation of these methodologies for exploring further mitigation strategies. The steps that should followed to assess GHG emissions as well as the indices that may affect the final carbon footprint of livestock units are also noted. Parameters that also eliminate the comparison between studies that assess GHG emissions from livestock are discussed. Finally, some scenarios that could serve as mitigation strategies towards the impact of livestock on climate change at the country level are highlighted.